FOOD PRODUCTS DATABASE: TRANSNATIONAL APPLICATION PROBLEMS - L. M. Bugyna,; O. V. Pallah; T.V. Meleshko; V. V. Bati; N.V. Koval; N.V. Boyko (Biotechnologia Acta, 2019)
The purpose of this study was to analyze and compare the existing international methods applied for classifying and identifying foods characteristics in a number of modern computerized databases such as Foodex, INFOODS/FAO, EuroFIR, and present our initial results of Regional and National Ukrainian food composition databases creation.